KAJIAN HUKUM KEPAILITAN DI INDONESIA: Studi Putusan Nomor 36/Pdt.SusPailit /2020/ PN Niaga Jkt.Pst - Tan, David; Joseline, Joseline (Maleo Law Journal, 2022)
Debt is an obligation to pay an amount of money agreed and promised by both parties, but debt is often underestimated and not carried out in accordance with the rules so that a lawsuit for bankruptcy arises. A bankruptcy petition can be filed in court if it fulfills the requirements stipulated in Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. In addition to the declaration of bankruptcy, it can also be filed by the creditor against the debtor who does not pay his debt obligations to the commercial district court. Several lawsuits and applications have been submitted to the commercial court, one of which is the bankruptcy case that was tried at the Central Jakarta Commercial Court decision Number 36/Pdt.SusPailit/2020/PN Niaga Jkt.Pst. This study aims to analyze how the position case, the suitability of the reasons for filing this bankruptcy suit and the suitability of the judges' considerations in deciding the decision in this bankruptcy case. This research applies normative legal research methods. The results of the discussion produced in this study found that the reason for the judge in granting the case application submitted by PT. Pandega Design Weharima and CV. Media Konsultindo has complied with the facts and applicable laws